ANALYSIS OF THE EIGHTH GRADE STUDENTS LEARNING STYLES AND PERSONALITY TYPES IN LEARNING ENGLISH AT STATE JUNIOR HIGH SCHOOL MUHAMMADIYAH 3 TRIYOSO - Amalia Khoirunisa; Hermansyah; Asti Veto Mortini (Universitas PGRI Palembang, 2024)
This research aims to analyze and determine the relationship between learning styles and personality types of the eighth grade students at SMP Muhammadiyah 3 Triyoso. Learning style is understood as an individual's preferences in gathering, processing, and remembering information, while personality type refers to consistent behavioral patterns and psychological characteristics that influence the way a person interacts with their environment.. The research method used was a descriptive qualitative study with a sample of 30 students from class VIII A. The instruments used consisted of questionnaires and interviews. The data collected was analyzed using descriptive statistical techniques and correlation analysis to identify patterns of relationships between learning styles and personality types. The research results show a significant correlation between several learning style dimensions for example visual learning styles (66%) auditory learning styles (33%) and kinesthetic learning styles (6%) and certain personality types such as Introvert and Extrovert. These findings provide valuable insights for more personalized and effective learning approaches in the school environment. This study makes an important contribution to our understanding of how learning styles and personality types influence each other in the context of higher education. The implications of this research can be used to develop learning strategies that are more focused and based on individual uniqueness, with the aim of increasing the effectiveness of learning and teaching.